Refusing care forced treatment and the rights of the mentally ill - Saks, Elyn R., 1955- (Chicago, Ill. ; London : University of Chicago Press, 2002)
Focusing on overinterventionist approaches, 'Refusing Care' asks when, if ever, the mentally ill should be treated against their will. Saks proposes standards that, as much as possible, should apply equally to non-mentally ill and mentally ill people.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Involuntary treatment; Mental illness -- Treatment; Health and Wellbeing; United States of America, USA; Social services & welfare, criminology; Psychology; Jurisprudence & general issues; Social law & Medical law